Hematophagous insects as vectors for frog trypanosomes - Ramos, Bricio (1977)
Experimental infections of three hematophagous arthropods (Rhodnius prolixus, Aedes aegypti, and Culex pipiens) with a trypanosome of the Trypanosoma rotatorium complex found in the frogs Hyla crepitans and Leptodactylus insularum revealed that A . aegypti is a good host for the flagellate; the course of development in the intestinal tract of the mosquito is described from 15 minutes to 168 hours. C. pipiens showed only low intestinal infections and R. prolixus did not permit development of the parasite. It is postulated that, in addition to the transmission of T. rotatorium by leeches, batrachophilie mosquitoes may transmit the parasite to frogs of more terrestrial habits by being ingested by these anurans.